Traditional Games as a Tools for Increasing Students' Motor Skills and Effort to Preserve The National Culture: Traditional Games as a Tools for Increasing Students' Motor Skills and Effort to Preserve The National Culture - sujarwo jarwo; Sudardiyono Sudardiyono; Hari Yuliarto Yuliarto; Yudanto Yudanto (UNUSA Press, 2021)
Teachers have difficulty understanding the material about traditional games and sports (TSG). A preliminary study showed that some kindergarten teachers had not received material about TSG, so they are tough to implement them. Training on traditional games helps teachers to reintroduce and socialize them in schools. This community service method was material presentation and discussions using a website seminar (webinar) through the zoom application on 40 kindergarten teachers in Bantul district, Yogyakarta. The results showed that the mean/average difference in teacher comprehension before and after community service was 68.50 and 85.75, respectively. There was an increase in the teacher's understanding that traditional games can improve children's motor skills and make an effort to preserve the nation's ancestors' heritage. The conclusion shows that most Kindergarten teachers can understand the concept and application of traditional games to increase fine and gross motor skills of kindergarten students and indirectly maintain ancestral culture to strengthen the nation. Teachers have difficulty understanding the material about traditional games and sports (TSG). A preliminary study showed that some kindergarten teachers had not received material about TSG, so they are tough to implement them. Training on traditional games helps teachers to reintroduce and socialize them in schools. This community service method was material presentation and discussions using a website seminar (webinar) through the zoom application on 40 kindergarten teachers in Bantul district, Yogyakarta. The results showed that the mean/average difference in teacher comprehension before and after community service was 68.50 and 85.75, respectively. There was an increase in the teacher's understanding that traditional games can improve children's motor skills and make an effort to preserve the nation's ancestors' heritage. The conclusion shows that most Kindergarten teachers can understand the concept and application of traditional games to increase fine and gross motor skills of kindergarten students and indirectly maintain ancestral culture to strengthen the nation.